2006
DOI: 10.1002/ppul.20550
|View full text |Cite
|
Sign up to set email alerts
|

Airway pressure release ventilation: A pediatric case series

Abstract: Summary. Airway pressure release ventilation (APRV) is a relatively new mode of mechanical ventilation (MV) first described in animal studies in 1987 and in humans in 1988. It is a timetriggered, time-cycled, pressure-limited mode where a high level of continuous positive airway pressure (CPAP) is maintained with brief regular releases in pressure, and spontaneous breathing is allowed throughout the cycle. In theory, it is consistent with a lung protective approach while having some hypothetical advantages ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…Data obtained from present cases support the notion that APRV can improve oxygenation in some children with AHRF as in Krishan case series [9]. Krishan et al showed that oxygenation index improved in several of their patients managed with APRV but there was no data about lung mechanics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Data obtained from present cases support the notion that APRV can improve oxygenation in some children with AHRF as in Krishan case series [9]. Krishan et al showed that oxygenation index improved in several of their patients managed with APRV but there was no data about lung mechanics.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies and case reports in adult patients suggest that APRV provides a benefit by allowing oxygenation and ventilation to patients with acute lung injury (ALI) and ARDS [1][2][3][4][5]. There is limited data about the benefits of APRV in children [8][9][10]. In this paper, authors have presented three patients with AHRF whose oxygenation did not improve with conventional ventilation and were treated with APRV.…”
Section: Introductionmentioning
confidence: 88%
“…To be effective, these modes can require a mean airway pressure 5 cmH 2 O higher than that used with conventional ventilation. This can reduce venous return leading to greater need for fluid resuscitation and vasopressor requirements [612][613][614][615][616].…”
Section: Mechanical Ventilationmentioning
confidence: 99%
“…This can reduce venous return leading to greater need for fluid resuscitation and vasopressor requirements (612)(613)(614)(615)(616). Some patients with ARDS will require increased PEEP to attain functional residual capacity and maintain oxygenation, and peak pressures above 30 to 35 cm H 2 O to attain effective tidal volumes of 6 to 8 mL/kg with adequate CO 2 removal.…”
Section: Mechanical Ventilationmentioning
confidence: 99%